Afirmasi Positif Terhadap Self-Esteem Mahasiswa Korban Bullying Di Universitas X Cirebon - Herman Beni (UIN Siber Syekh Nurjati Cirebon, 2025)
Mental health is important for students to be able to study with focus, creative thinking, and productive. This research is based on the impact of bullying which can lower the self-esteem of students. Victims of bullying often feel worthless, lack confidence, and withdraw from the social environment. This research aims to find out the self-esteem condition of students who are victims of bullying at X Cirebon University, risk and protective factors that affect it, as well as the impact of positive affirmation on improving self-esteem. The method used is qualitative with a case study approach, involving three students from the Islamic Counseling Guidance Study Program as informants. The research results show that before undergoing positive affirmation, the informant experiences low self-esteem, feels unworthy, not confident, and alienated. Risk factors include the mockery of friends, an unsupportive environment, and traumatic experiences. However, they also have protective factors such as family support, close friends, and self-motivation. After undergoing regular positive affirmations, the informant shows increased self-confidence, self-acceptance, and a more positive mindset. Positive affirmations are proven to help increase self-esteem and support the psychological recovery of students who are victims of bullying.